2010
DOI: 10.1021/ja100252y
|View full text |Cite
|
Sign up to set email alerts
|

Functional Hyperbranched Polymers: Toward Targeted in Vivo 19F Magnetic Resonance Imaging Using Designed Macromolecules

Abstract: We have demonstrated the design and synthesis of hyperbranched molecules that can be successfully imaged in vivo using (19)F MRI in under 10 min. These polymers are cytocompatible following chain extension with PEGMA. In addition, functionalization of these macromolecules can be achieved in a facile manner and with accessible and correct ligand presentation. Such hyperbranched polymers hold promise as new generation tracking and targeting MRI contrast agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
240
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(243 citation statements)
references
References 13 publications
3
240
0
Order By: Relevance
“…[267] Pressley et al [611] have reported on an improved methodology for conducting click reactions to form block and cyclic polymers. [227] PFPMA/LMA Ph AIBN 25 70 100 [225] BA Ph AIBN 30 80 ,25 [194] HA Ph ACPA 5 70 100 [240] HA Ph AHPN 5 70 100 [240] BA/NA Ph AIBN 20 80 100 [202] BA C 4 H 9 S AIBN 30 80 ,25 [194] BA C 4 H 9 S AIBN þ BPO 20 þ 2 E 80 100 [194] HPA [596] tBA Poly(tBA)S AIBN -80 100 [597] NIPAm Poly(tBA-b-NIPAm)S AIBN -80 100 [597] tBA/TBBPMA Ph AIBN (20) (80) 100 [598] DAMEA/TFEA C 12 H 25 S AIBN 20 65 100 [599] HADA [194] St Ph AIBN þ BPO 20 þ 2 E 80 100 [194] St C 4 H 9 S AIBN 30 À 100 80 ,60 [194] St C 12 H 25 S AIBN 10 95 92 [393] A Monomer unit adjacent to thiocarbonylthio group. The process makes use of commercially available copper nanoparticles and is performed with microwave irradiation.…”
Section: Click Reactionsmentioning
confidence: 99%
“…[267] Pressley et al [611] have reported on an improved methodology for conducting click reactions to form block and cyclic polymers. [227] PFPMA/LMA Ph AIBN 25 70 100 [225] BA Ph AIBN 30 80 ,25 [194] HA Ph ACPA 5 70 100 [240] HA Ph AHPN 5 70 100 [240] BA/NA Ph AIBN 20 80 100 [202] BA C 4 H 9 S AIBN 30 80 ,25 [194] BA C 4 H 9 S AIBN þ BPO 20 þ 2 E 80 100 [194] HPA [596] tBA Poly(tBA)S AIBN -80 100 [597] NIPAm Poly(tBA-b-NIPAm)S AIBN -80 100 [597] tBA/TBBPMA Ph AIBN (20) (80) 100 [598] DAMEA/TFEA C 12 H 25 S AIBN 20 65 100 [599] HADA [194] St Ph AIBN þ BPO 20 þ 2 E 80 100 [194] St C 4 H 9 S AIBN 30 À 100 80 ,60 [194] St C 12 H 25 S AIBN 10 95 92 [393] A Monomer unit adjacent to thiocarbonylthio group. The process makes use of commercially available copper nanoparticles and is performed with microwave irradiation.…”
Section: Click Reactionsmentioning
confidence: 99%
“…Recently, RAFT has been applied in synthesis of classic hyperbranched or core cross-linked star polymer nanocontrast agents, which has demonstrated good control of polymer structure. [36][37][38]44,45 The novel dimethacrylate cross-linker 6 employed incorporates the DO3A macrocycles simultaneously during the branching process ensuring the DO3A macrocycles are …”
Section: Synthesis Of Branched Copolymer Nanoparticles Via Raft Polymmentioning
confidence: 99%
“…More recently, there has been an increase in literature reports of experimental studies which have exploited these properties of hyperbranched polymers in a vast array of medical applications, 2 including gene delivery, [18][19] drug delivery, 20 bio-surfaces modification, 21 and molecular imaging. [22][23] In the field of biomedical polymers, polyesters are a class of material which find particular utility. This is because of their good thermal and mechanical properties, acceptable levels of chemical resistance, ease of synthesis, availability of monomer feed stocks and many are defined to be biodegradable.…”
Section: Introductionmentioning
confidence: 99%